Application of genipin-crosslinked small intestine submucosa and urine-derived stem cells for the prevention of intrauterine adhesion in a rat model. (1st February 2023) - Song, Yu-Ting; Dong, Li; Hu, Jun-Gen; Liu, Peng-Cheng; Jiang, Yan-Lin; Zhou, Li; Wang, Min; Tan, Jie; Li, Ya-Xing; Zhang, Qing-Yi; Zou, Chen-Yu; Zhang, Xiu-Zhen; et al.
Abstract: As a major cause for recurrent miscarriage and secondary infertility, intrauterine adhesion (IUA) is characterized by partial or total obliteration of the uterine cavity and/or cervical canal due to injuries to the basal layer of endometrium caused by improper intrauterine operation and/or infection. While various treatments have been used to prevent the occurrence of IUA, these approaches have shown limited therapeutic efficiency. As a promising bio-engineering method, tissue engineering technology may be used for enhancing endometrial regeneration. Extracellular matrix such as small intestine submucosa (SIS) may provide a favorable microenvironment, whilst stem cells can promote the endometrial regenerative capacity. In this study, genipin-crosslinked SIS (GP-SIS) loaded with urine-derived stem cells (USCs) has been applied for the regeneration of endometrium. The GP-SIS scaffolds have demonstrated sound mechanical properties and excellent biocompatibility and promoted epithelial migration and angiogenesis in vitro . In a rat model for IUA caused by endometrial damage, transplantation of the GP-SIS/USCs has maintained normal luminal structure, promoted endometrial and glandular regeneration, vascularization, inhibited fibrogenesis and improved endometrial receptivity. Our research has therefore provided a new strategy for promoting the recovery of endometrial structure and function, which may be beneficial for the prevention and treatment of IUA in the clinics. Graphical abstract: Image 1